Spatial Variability of Urban Heat Island of Sargodha City in Pakistan - Sajjad Hussain Sajjad; Sadaf Hussain; Safdar Ali Shirazi; Khadija Shakrullah; Khuram Shahzad; Rabia Batool; S.M. Talha Qadri (Journal of Basic & Applied Sciences, 2015)
Sargodha is one of the most important cities of Pakistan. Located in the center of Pakistan, it is the hub of the Pakistan Air Force. Rapid urbanization in the city has caused it to expand it farther from its center. Sargodha is 11th most populated metropolitan city in Pakistan. Currently, it has 0.7 million population and covers an area of 52 km2. The objective of this study was to measure the spatial variability of urban heat island (UHI) in different areas of the city in comparison with the temperature of the urban center. The meteorological data was measured by installing digital weather stations at four sites, 3 within the city by considering the areas as urban highly dense, urban less dense and urban periphery and one at rural site almost 10 km away from the city center. The result highlighted that difference in temperature between urban densely built area and rural site was highest. The difference in temperature increased as one moved away from the city center where urban areas were found warmer than the sites comparatively away from the city center. It was observed that the UHI intensity is not same in different areas of the city. The highest intensity of UHI is observed on Sunday where it was measured 5.7 °C.